ESPRESSO: The next European exoplanet hunter. Issue 1 (January 2014) - Pepe, F.; Molaro, P.; Cristiani, S.; Rebolo, R.; Santos, N.C.; Dekker, H.; Mégevand, D.; Zerbi, F.M.; Cabral, A.; Di Marcantonio, P.; Abreu, M.; Affolter, M.; et al.
Abstract The acronym ESPRESSO stems for Echelle SPectrograph for Rocky Exoplanets and Stable Spectroscopic Observations; this instrument will be the next VLT high resolution spectrograph. The spectrograph will be installed at the Combined‐Coudé Laboratory of the VLT and linked to the four 8.2 m Unit Telescopes (UT) through four optical Coudé trains. ESPRESSO will combine efficiency and extreme spectroscopic precision. ESPRESSO is foreseen to achieve a gain of two magnitudes with respect to its predecessor HARPS, and to improve the instrumental radial‐velocity precision to reach the 10 cm s–1 level. It can be operated either with a single UT or with up to four UTs, enabling an additional gain in the latter mode. The incoherent combination of four telescopes and the extreme precision requirements called for many innovative design solutions while ensuring the technical heritage of the successful HARPS experience. ESPRESSO will allow to explore new frontiers in most domains of astro‐physics that require precision and sensitivity. The main scientific drivers are the search and characterization of rocky exoplanets in the habitable zone of quiet, nearby G to M‐dwarfs and the analysis of the variability of fundamental physical constants. The project passed the final design review in May 2013 and entered the manufacturing phase. ESPRESSO will be installed at the Paranal Observatory in 2016 and its operation is planned to start by the end of the same year. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)